IMPLEMENTATION OF SMART TECHNOLOGIES IN THE JUDICIAL SYSTEM: FOREIGN EXPERIENCE OF IMPLEMENTATION - Banakh, Serhiy; Kovalchuk, Olha (Актуальні проблеми правознавства, 2026)
The article examines foreign experience in implementing smart technologies in judicial systems. The relevance of digital transformation of justice, driven by the need to increase efficiency and transparency of judicial proceedings, has been analyzed. The most common forms of smart technological solutions are being examined within contemporary judicial processes. It has been determined that online dispute resolution systems are actively used in the Netherlands, the United Kingdom, the USA, India, China, Kazakhstan, through international platforms eBay, Smartsettle, Virtual Courthouse, and Modria. Blockchain technologies and smart contracts are utilized to automate the fulfillment of contractual obligations. However, their implementation gives rise to new types of disputes due to the complexity of interpretation and technical vulnerabilities. China’s experience as a pioneer in creating virtual “internet courts” has been highlighted. It is noted that since 2022, Chinese judges have been required to consult with artificial intelligence systems when considering cases. The system has access to government agency databases and controls the execution of court decisions. However, the Chinese model creates risks of violating the principles of separation of powers and strengthening state control. Unique foreign practices have been analyzed: court proceedings in the metaverse in Colombia, the use of ChatGPT by British judges for writing decisions, the virtual enforcement court in Saudi Arabia, and the Italian mobile application “Collega” for finding lawyers. Digitalization strategies of Kazakhstan (Torelik portal), Brazil (100% digital court), India (virtual courts for minor disputes), the Netherlands (Virtual Court platform), and the USA (virtual courtrooms) have been studied. It is emphasized that the choice of technologies depends on the characteristics of national judicial proceedings, legislation, and technological capabilities of the country. Recommendations for Ukraine have been formulated regarding the implementation of an online dispute resolution system based on the experience of the Netherlands and the USA, specialized applications for legal assistance to military personnel and internally displaced persons. The need for comprehensive legal regulation to maximize advantages (accessibility of justice, transparency, reduction of corruption) and minimize threats (technical failures, cybercrime, algorithm biases, violation of the right to a fair trial) has been emphasized.